Rethinking International Order According to Islamic International Relations Principles - Md Ramzan, Muhammad Fahmi; Abdul Rahman, Mohamad Zaidi; Mohd Daud, Nurfarhana (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2022)
The world today needs to recognise the differences and varieties of religions, cultures., societies and economies among countries. It is necessary for states and nations to uphold the law towards a common purpose, i.e. to regulate life in peace and harmony. Similarly, an international order will establish an allied world government or a coalition of allies with the executive machinery that is necessary for its implementation. This government will be supported by the international law in place that can be utilised by all, regardless of governments, institutions, communities or individuals. Therefore, the world today needs to re-establish an international order that would result in a peaceful and rational in fulfilling human needs. Thus, this article elaborates on the international order from anIslamic perspective and notes that Islam has introduced effective principles which are suitable and acceptable to all communities.